Indicators of Household Pottery Production: A Case-Study from the Chupicuaro Formative Culture. (17th August 2020) - Darras, Véronique; Hamon, Caroline
ABSTRACT: Despite their reputation, little work has been carried out on Chupícuaro ceramics, and the organization of pottery production and its role in the economy of these populations are still poorly known. The excavations of the Chupícuaro project did not identify any pottery production areas, but uncovered fired clay coils and plaques and hard stone artifacts in the site of Cuizillo de Don Fidel Salinas (TR. 6). The techno-morphological study of these artifacts and the use-wear analysis of a sample show that they were specialized potters' tools, designed to be adapted to the technical requirements of the composite shapes and used at specific stages of the chaîne opératoire. Moreover, contextual data show that pottery making was carried out in a domestic setting. This article places the tools at the core of the debate and shows that they can be an essential marker for identifying areas of ceramic production in Mesoamerica.